Combining actor-network theory with interventionist research: present state and future potential - Lukka Kari; Vinnari Eija (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose - The purpose of this paper is to examine the philosophical and practical compatibility of actor-network theory (ANT) and interventionist research (IVR) and search for explanations for their scant combined use. The scope of investigation is limited to accounting, management and organization studies (MOS), but the findings are believed to be applicable in other social sciences as well.
Design/methodology/approach - An analysis is conducted of accounting and MOS research in addition to interviewing eight accounting scholars who have applied IVR and/or ANT in their research.Findings - A comparison of the philosophical and other features of ANT and IVR suggests that they should be relatively easily combinable in studies. Based on interview material, three types of barriers to combining ANT and IVR are identified: perceived epistemological incompatibility, fear of going native or losing neutrality and academic tribes. However, subsequent analysis indicates that none of these forms an insurmountable obstacle to the combination.
Research limitations/implications - The combined application of ANT and IVR could benefit both IVR and ANT researchers in management accounting as it would enable them to conduct theoretically grounded studies on dynamic processes, such as the emergence and implementation of accounting innovations, to pose original research questions and to find new perspectives to accounting phenomena.
Practical implications - Employing ANT and IVR in combination could increase organizational interest in management accounting research.
Originality/value - The paper contributes to the discussion on the compatibility of different research approaches and highlights ways in which researchers could benefit from combining ANT and IVR.